The enabling environment for disaster risk financing in Nepal country diagnostics assessment. (Asian Development Bank, 2019)
It explores the current application of disaster risk financing solutions by the government, businesses, and individual households; related demand and supply constraints; and opportunities for improvement. The assessment forms one of a series of country diagnostics undertaken using a common methodology to determine the state of the enabling environment for disaster risk financing.